Comparison the reactive capability of propargyl radical (C₃H₃) to ammonia (NH₃) and methyl radical (CH₃) in the gas phase - Pham, Van Tien; Nguyen, Ngoc Tue (Old Journal, 2017)
The reaction mechanisms between propargyl radical and ammonia (NH₃) or methyl radical (CH₃) have been studied by the Density Functional Theory (DFT) using the B3LYP functional in conjunction with the 6-311++G(3df,2p) basis set. Our calculations show that the C₃H₃ + NH₃ reaction has two main entrance channels: H-abstraction and addition while the other has only one type of entrance which is addition. If two additional reaction pathways of C₃H₃ + NH₃ have relative energies (kcal·mol⁻¹) that are found to be fairly high, the two additional directions of C₃H₃ + CH₃ have no transition states at the beginning of entrance. In terms of thermodynamic side, all of products are possible to be produced at the investigated condition, in which the product P₂ (HCCCH₃ + NH₂) of the first system and P₆ (C₂H₂ + C₂H₄) of the second reaction are the most favorable. Besides, the analytical results of energies showed that the C₃H₃ + CH₃ reaction takes place more easily compared to the C₃H₃ + NH₃ system.